2017
DOI: 10.24071/jpsc.142858
|View full text |Cite
|
Sign up to set email alerts
|

ANTI-INFLAMMATORY AND ANALGESIC ACTIVITIES OF AVOCADO SEED (Persea americana Mill.)

Abstract: The purpose of this research is to evaluate the anti-inflammatory and analgesic activities of infusion and methanolic extract from avocado seeds. The anti-inflammatory activity was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The results obtained in the rat paw edema show that the active principles present in the avocado peel may act analogously in the inflammatory response produced by carrageenan. These results are similar with a previous report in which the same doses of avocado seed infusion and extract had antiinflammatory activities (Kristanti et al, 2017). Avocado leaves also possess anti-inflammatory activity (Adeyemi et al, 2002).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The results obtained in the rat paw edema show that the active principles present in the avocado peel may act analogously in the inflammatory response produced by carrageenan. These results are similar with a previous report in which the same doses of avocado seed infusion and extract had antiinflammatory activities (Kristanti et al, 2017). Avocado leaves also possess anti-inflammatory activity (Adeyemi et al, 2002).…”
Section: Resultssupporting
confidence: 92%
“…Group II, as negative control group for avocado peel extract, were given CMC-Na, and group III, as positive control, were given Cataflam Fast® (Pottasium Diclofenac) 4.48 mg /kgBW. Groups IV -VI were given avocado peel infusion with 3 levels of doses, 667.5; 1335; and 2670 mg/kgBW (Kristanti et al, 2017). Groups VII -IX were given avocado peel decoction with 3 levels of doses which were 667.5; 1335; and 2670 Pharmaciana ISSN: 2088 4559; e-ISSN: 2477 0256…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the study of Daihan et al [42], avocado seed used in traditional medicine for the treatment of various ailments and has antibacterial, antifungal, anti-viral and woundhealing properties. They reported that, antioxidant potential of plant extracts was evaluated by means of total phenolic, total flavonoids content and DPPH radical scavenging activity.…”
Section: Egbuonu Et Al Reported That the Avocado Seed Extract (Ase)mentioning
confidence: 99%